2000
DOI: 10.1111/j.1469-8749.2000.tb00083.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of psychiatric diagnoses in children with mental retardation: data from a population‐based study

Abstract: The main purpose of the study was to estimate the prevalence of psychiatric diagnoses in children with mental retardation (MR) (IQ≤70). All children born between 1980 and 1985 (N=30037) in Akershus County, Norway, were screened for possible MR and assessed with either IQ tests or standardized developmental tests. A total of 178 children, 79 with severe mental retardation (SMR) (IQ<50) and 99 with mild mental retardation (MMR) (IQ 50 to 70) were included for further study. Psychiatric symptomatology was assesse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
63
1
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(75 citation statements)
references
References 24 publications
10
63
1
1
Order By: Relevance
“…The results add to the existing body of literature that suggests that (older) age, (more restricted) adaptive behaviour and (male) gender are associated with higher risk of emotional and behavioural disorders (Einfeld & Tonge 1996a,b;Stromme & Diseth 2000;Emerson 2003;. They are also consistent with the very limited literature on ethnic differences in finding that teachers report lower rates of emotional and behavioural disorders among South Asian children .…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…The results add to the existing body of literature that suggests that (older) age, (more restricted) adaptive behaviour and (male) gender are associated with higher risk of emotional and behavioural disorders (Einfeld & Tonge 1996a,b;Stromme & Diseth 2000;Emerson 2003;. They are also consistent with the very limited literature on ethnic differences in finding that teachers report lower rates of emotional and behavioural disorders among South Asian children .…”
Section: Discussionsupporting
confidence: 86%
“…First, a number of studies have sought to identify the prevalence of emotional and behavioural needs in wellconstructed population-based samples. The available evidence from this strand of research suggests preval-ence rates of approximately 40% for emotional and behavioural disorders (including formally diagnosed psychiatric disorders) among young people with intellectual disabilities in Australia (Einfeld & Tonge 1996a,b), England (Emerson 2003), Finland (Linna et al of intellectual disabilities, communication skills, physical disability (Einfeld & Tonge 1996a,b;Stromme & Diseth 2000;Emerson 2003) -and increasingly on the impact of syndromes associated with intellectual disabilities on emotional and behavioural needs (Dykens 1999;Hodapp & Dykens 2004). There also exists a modest literature on the impact of proximal social factors, such as family characteristics and functioning (Emerson 2003) and life events (Hatton & Emerson 2004) on prevalence rates.…”
Section: Introductionmentioning
confidence: 99%
“…However, the rate of mental health problems in our sample was higher than reported by other studies on mental health problems in people with ID. International studies have reported the prevalence of mental health problems to be 31-50% in children and adolescents with ID (Dekker & Koot, 2003;Dekker, Koot, van der Ende, & Verhulst, 2002;Emerson, 2003;Emerson & Hatton, 2007;Linna et al, 1999;Molteno, Molteno, Finchilescu, & Dawes, 2001;Strømme & Diseth, 2000). Cooper et al (2007) concluded that the prevalence of mental health problems in adults with ID is 16-41%, and in adults with MID the prevalence is 34.4%.…”
Section: Discussionmentioning
confidence: 99%
“…Autism spectrum disorder (ASD) is one of the most common neurodevelopmental disorders occurring in 1 out of 68 children (Centers for Disease Control and Prevention [CDC] 2014a) and is the second most common comorbid disorder with ID after ADHD (Strømme and Diseth 2000). According to the Diagnostic and Statistical Manual of Mental Disorders (5th ed.…”
Section: Autism Spectrum Disorders and Idmentioning
confidence: 99%